Implementing Laravel Framework for E-Commerce: Case Study at Indonesian Farmer Shop Center - Defni, -; Lestari, Tri (SOTVI, 2020)
This paper aims to implement e-commerce using the laravel framework. The implementation of e-commerce is applied to the Indonesian Farmer Shop Center (TTIC) in the city of Padang, especially in the sales section precisely sales and payment transactions. This e-commerce can make it easier for consumers to purchase products in TTIC. For making e-commerce using the laravel framework. For e-commerce creation use the laravel framework. Its data storage uses a MySQL database.This paper aims to implement e-commerce using the laravel framework. The implementation of e-commerce is applied to the Indonesian Farmer Shop Center (TTIC) in the city of Padang, especially in the sales section precisely sales and payment transactions. This e-commerce can make it easier for consumers to purchase products in TTIC. For making e-commerce using the laravel framework. For e-commerce creation use the laravel framework. Its data storage uses a MySQL database.